PARLIAMENT SHAPES AND SIZES. (6th May 2018) - Godefroy, Raphael; Klein, Nicolas
Abstract : This paper proposes a model of Parliamentary institutions in which a society makes three decisions behind the veil of ignorance: whether a Parliament should comprise one or two chambers, what the relative bargaining power of each chamber should be if the Parliament is bicameral, and how many legislators should sit in each chamber. We document empirical regularities across countries that are consistent with the predictions of our model. ( JEL D71, D72)